Exploring leadership personality: A key for higher education transformation - Tessie H.H. Herbst (Transformation in Higher Education, 2025)
Leadership plays a critical role in organisational transformation and is strongly shaped by leaders’ personalities and the organisational culture of collective behaviours, attitudes, and values. Literature has indicated that executives’ personalities are an important factor impacting organisational strategy and structure. Organisational culture, often considered the ‘fingerprint’ of leadership, reflects the organisation’s collective personality. This article examines leadership and organisational personality through the combined results of the iEQ9 Enneagram personality assessment, conducted with 89 middle and senior academic leaders at a South African university between 2020 and 2022. This research, conducted as part of a leadership development programme, examined how leader personality influences efforts to drive organisational transformation. The Enneagram personality framework was utilised as a lens for analysis. Quantitative descriptive analysis was used to interpret and discuss leader personalities and their potential impact on organisational culture and strategic leadership in transformation.